Skärpedjupets påverkan på trovärdigheten i nyhetsinslag på TV - Bergström, Mattias; Lindgren, Oskar (2012)
This study investigates the use of depth of field in segments of a news programmes, also called news videos, and the perceived experience of the audience. The research problem is related to how depth of field can influence the perception of the audience in relation to credibility, presence and qualification. The study is based on the increased use of DSLR cameras for daily newspapers when producing television meant for the internet. Using DSLR cameras results in a shorter depth of field than a video camera would produce in an equal situation.In a between subjects experiment, two identical news videos were produced where only the depth of field separated them as a sole factor. The information and the picture compositions in both videos remained almost identical which allowed us to examine only the depth of field as a sole factor. To gain background information in the matter an interview with a producer was performed and calls were made to newspapers to map out the camera equipment. In addition an empirical collection of news videos were also investigated. Two larger screenings were carried out for students at Luleå University of Technology in relation to course introductions. One group of students were shown the news video with a short depth of field and the other group viewed the one with a long depth of field. The larger screenings resulted in fewer participants than expected. Therefore complement screenings were carried out in the same type of environment in smaller groups of two to three participants until the number of participants were sufficient. The study consisted in a total of 82 subjects, which means 41 participants in each group.After the screening the participants were asked to fill in a survey which covered the variables credibility, qualification and sensation of presence. The survey consisted of a number of sub questions which in total were used to describe each variable. A t-test were performed as a method of analysis for each of the variables using SPSS.The final result does not demonstrate any ...